2021
DOI: 10.1007/s11069-021-04913-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying climate-induced drought risk to livelihood and mitigation actions in Balochistan

Abstract: Climate change-induced disasters show the highest risk for agriculture and livelihoods in rural areas of developing countries. Due to changing rainfall pattern, the arid and semiarid region of Pakistan faces frequent droughts. Farming communities affected by drought disasters are causing serious threats to livelihood, global food crises, environmental migration, and sustainable development. The existing study was designed to quantify two key components through (1) analysis of agrometeorological data (1981-2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Pakistan is ranked 17th among the most-scarce countries in the world, and 79% of potable water is not safe for drinking purposes (Ashraf et al, 2021). Water availability in Pakistan has been decreased from 1,300 m 3 /person (1996)(1997) to 1,100 m 3 /person (2006) and expected to decrease further to less than 700 m 3 /person in 2025 (Roxy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is ranked 17th among the most-scarce countries in the world, and 79% of potable water is not safe for drinking purposes (Ashraf et al, 2021). Water availability in Pakistan has been decreased from 1,300 m 3 /person (1996)(1997) to 1,100 m 3 /person (2006) and expected to decrease further to less than 700 m 3 /person in 2025 (Roxy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The issues and challenges about the education, and awareness to undertake adaptation approaches in face of climate change aiming ensuring food security are multidimensional, and recent studies have concentrated on several limitations to the climate change awareness and the adjustments besides apparent climatic and non-climatic agents of climate vulnerability, mainly in the developing and underdeveloped countries. Several studies have recommended that in face of climate variabilities, experiences are induced by both climatic (drought, temperature, floods) and non-climatic elements (limited availability of agricultural equipment and technologies, and reduced income) and therefore, it turns to be highly difficult to apprehend the intermix of such variables that aggravate the vulnerabilities of households against climate change ( Jamshidi et al, 2019 ; Ashraf et al, 2021 ; Shah et al, 2021 ).…”
Section: Future Directions Suggestions and Challenges In Action Agendamentioning
confidence: 99%
“…A large number of scholars have successively carried out research on climate change vulnerability and risk. These studies used vegetation and ecological models and other simulation studies [6][7][8], indicators to assess climate change vulnerability and risk [9] or focused on adaptation measures and technological innovations for climate change risks [10][11][12][13]. Budiyono et al [6] used vulnerability curves and flood risk assessment models; considered local factors related to hazards, exposure and vulnerability; assessing flood risk in Jakarta quantitatively, and they found that Jakarta is estimated to lose approximately US$321 million annually due to river flooding.…”
Section: Introductionmentioning
confidence: 99%